In Her Words: Translating Womanhood - Priego Becerra, Samantha (Trinity College Dublin, School of Languages, Literatures and Cultural Studies, 2024)
The texts included in this translation portfolio are written by women from a variety of geographical contexts, including Antigua, Ecuador, México, Sudan, and others. The texts span from 17th century precolonial México to the present day. In the first text, Olivia Gatwood imagines a metaphorical dead girl to reflect on true crime. Followed by Mónica Ojeda’s short story about flying women in the countryside of Mira, Ecuador. Jamaica Kincaid denounces the endless rules of domestic housework, while Alejandra Eme Vázquez creates a framework to talk about care and domestic work. In the contrapuntal poem “yasmeen”, Safia Elhillo grieves the girl she could have been, whereas Sor Juana Inés de la Cruz uses the sonnet form to portray her yearning for knowledge. Jean Rhys presents a portrayal of colonial discrimination through a Martiniquais woman who speaks patois. Lastly, Mariana Enriquez draws inspiration from the real and violent landscape of Latin America to create a world where women are driven to set themselves on fire. These texts collectively explore the experiences of womanhood across varied contexts, reflecting on themes of identity, oppression, and resilience. This translation portfolio aims to capture the richness of this diversity, rendering it in and transposing it to different contexts in order to underscore the multiplicity inherent in these narratives.